Polish regulatory system regarding ATMP hospital exemptions - Pachocki, Jan; Verter, Frances (Frontiers in Immunology, 2024)
Introduction This article explains the current regulatory system in Poland regarding Advanced Therapy Medicinal Products given under Hospital Exemptions (ATMP-HE). Methods The relevant sections of Polish legislation are translated into English and their interaction is described. Results We analyze the impact of these regulations from the perspective of three stakeholder groups: manufacturers, physicians, and patients. Amendments enacted between 2018 and 2023 have substantially changed Polish implementation of the ATMP-HE pathway. In Poland, most ATMP-HE treatments have been therapies employing Mesenchymal Stromal Cells (MSC). Discussion Comparison to other European countries shows that Poland is within the mainstream of EU practices regarding ATMP-HE implementation. One notable issue is that Poland has relatively low per capita spending on healthcare, and ATMP-HE in Poland must be funded from outside the government healthcare system. Conclusions. The original intention of the legislation that created ATMP-HE was to allow access to experimental therapies for patients with unmet needs. It remains to be seen if that mission can be fulfilled amidst conflicting pressures from various stakeholder groups.